Kelayakan Bisnis dari Aspek Sumber Daya Manusia pada Pembangunan Hotel di Bogor - Hambali, Hasan; Dinitri, Seruni (Stupa, 2023)
The human resource aspect is one of the important aspects in a business feasibility study. Therefore, as one of the business functions called human resource management, human resources must be managed properly in order to increase the effectiveness and efficiency of the organization. This research methodology uses a qualitative descriptive method. The results of the analysis show that human resources include planning human resource personnel totaling 74 people with details of 46 employees and 28 daily employees. The organizational structure that explains the responsibilities of each department and the planning of wages in one month is Rp. 274.950.000. The conclusion from the above analysis can be concluded that the Bogor hotel seen from the human resources is feasible to build and the planned human resources are in accordance with the needs of three-star hotels.